2021
DOI: 10.3390/microorganisms9040786
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Drug-Resistance Genes of blaOXA-23-blaOXA-51 and mcr-1 in Clinical Isolates of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa has caused high rates of mortality due to the appearance of strains with multidrug resistance (MDR) profiles. This study aimed to characterize the molecular profile of virulence and resistance genes in 99 isolates of P. aeruginosa recovered from different clinical specimens. The isolates were identified by the automated method Vitek2, and the antibiotic susceptibility profile was determined using different classes of antimicrobials. The genomic DNA was extracted and amplified by multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
(72 reference statements)
0
16
0
2
Order By: Relevance
“…Carbapenem resistance in A. baumannii is most often mediated by acquired carbapenemase genes, particularly of the oxacillinase type, with blaOXA-23-like, blaOXA-24-like, blaOXA-58-like, blaOXA-143-like, and blaOXA-235-like genes being the most notable (2). Only blaOXA-58-like genes and blaOXA-23, which is the most widespread of the carbapenemase genes reported in clinical A. baumannii globally (42)(43)(44)(45)(46), were detected in the isolates in this study. blaOXA-58 had not previously been reported in Nigeria, and blaOXA-23 has been reported in only two Nigerian studies (15,16).…”
Section: Discussionmentioning
confidence: 50%
“…Carbapenem resistance in A. baumannii is most often mediated by acquired carbapenemase genes, particularly of the oxacillinase type, with blaOXA-23-like, blaOXA-24-like, blaOXA-58-like, blaOXA-143-like, and blaOXA-235-like genes being the most notable (2). Only blaOXA-58-like genes and blaOXA-23, which is the most widespread of the carbapenemase genes reported in clinical A. baumannii globally (42)(43)(44)(45)(46), were detected in the isolates in this study. blaOXA-58 had not previously been reported in Nigeria, and blaOXA-23 has been reported in only two Nigerian studies (15,16).…”
Section: Discussionmentioning
confidence: 50%
“…Pedersen et al (2018), relataram não ter encontrado evidências de que o gene mcr-1 seja a causa de resistência à colistina em P. aeruginosa, sendo dessa maneira associada, na maioria dos casos, a mutações que surgiram durante a terapia antimicrobiana de longo prazo. Contudo, apesar da baixa prevalência, P.aeruginosa mcr-1-positivo tem sido encontrada no Brasil e Paquistão como relatado respectivamente por Nitz et al (2021) e Hammed et al (2019.…”
Section: Resultsunclassified
“…On the other hand, the present study has also shown that MCR-1 mediated colistin resistance in P. aeruginosa has no impact on relevant physiological aspects, such as growth, drug sensitivity and cell envelope integrity, suggesting that there would be no fitness barriers to the spread of mcr genes in the P. aeruginosa population. This is an issue that deserves further investigation, especially in view of the recent identification of mcr harboring P. aeruginosa clinical isolates in different geographic areas ( Hameed et al, 2019 ; Abd El-Baky et al, 2020 ; Tahmasebi et al, 2020a , b ; Nitz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PEtN modification of lipid A was invariably observed in MCR-1 expressing strains and conferred colistin resistance, even though the resistance level varied significantly among different isolates and was overall much lower than that observed in other Gram-negative pathogens, such as Escherichia coli , Klebsiella pneumoniae , or A. baumannii ( Liu et al, 2016 , 2017 ). Interestingly, whilst until recently mcr plasmids were mainly found in Enterobacteriaceae, in the last couple of years some reports described the sporadic isolation of mcr -positive colistin resistant isolates of P. aeruginosa ( Hameed et al, 2019 ; Abd El-Baky et al, 2020 ; Tahmasebi et al, 2020a , b ; Nitz et al, 2021 ). Although these studies did not provide genetic and/or molecular evidence that mcr genes were indeed responsible for the colistin resistance phenotype, this body of evidence suggests that lipid A phosphoethanolamination could play a role in colistin resistance also in P. aeruginosa and, thus, that the contribution of endogenous and exogenous PEtN transferases to colistin resistance might be different in this bacterium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation